2005
DOI: 10.1109/tpwrd.2005.848448
|View full text |Cite
|
Sign up to set email alerts
|

A New Approach for the Computation of Harmonics and Interharmonics Produced by Line-Commutated AC/DC/AC Converters

Abstract: A new approach for modeling line-commutated ac/dc/ac conversion systems is presented and discussed. It is based on the modulation function theory taking advantage of a two-step procedure in which two different models are used. The goal is to achieve a reduction of the computational burden with respect to the time domain models and better modeling accuracy with respect to classical modulation function approaches. The proposed model constitutes an attractive tool inside Monte Carlo simulations for the probabilis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 19 publications
0
23
0
Order By: Relevance
“…This impedance involves both the conduction and the commutation conditions, so it depends on their duration, i.e., the overlapping angle m [1].…”
Section: Iterative Approachmentioning
confidence: 99%
See 3 more Smart Citations
“…This impedance involves both the conduction and the commutation conditions, so it depends on their duration, i.e., the overlapping angle m [1].…”
Section: Iterative Approachmentioning
confidence: 99%
“…This means to assume the mean value for the Z eq previously defined, so ignoring the modulation effects of the alternating of the rectifier conduction and commutation conditions [1]. In order to also take into account the effects of the rectifier conduction and commutation cycles on the supply side impedance as seen by the DC side, it is possible to consider again the circuit of Figure 2b), replacing the DC Equivalent Load by means of the series of the DC resistance and inductance and the e.m.f source v o'o (t) obtained at the end of the iteration process (Figure 7).…”
Section: (T)mentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have demonstrated that modern distributed energy resources, in particular wind turbines, are able to produce interharmonics in a wide range of frequency from DC to some kilohertz [15]. Moreover, in [16][17][18], it was demonstrated that interharmonic components produced by adjustable speed drives can cover all the frequency range from DC.…”
Section: Introductionmentioning
confidence: 99%